De facto versus de jure bank-insurance ventures in the Greek market - Kalotychou, Elena; Staikouras, Sotiris K. (My University, 2007)
The present study delves into the bank-insurance phenomenon in Greece. The paper explores the market-based practices surfacing through the bank-insurance interface and delineates the possible theoretical corporate structures. A review of the various financial ventures in the domestic market is provided aiming to unveil corporate patterns both in a cross-venture and time series framework. As a result of this survey, the existence of de jure limits versus de facto boundaries, as expanded by loopholes and avoidance activities, is established. The "traditional" subsidiary model is complemented by a number of multi-ventures as banks make inroads into the insurance business. The latter is associated with the presence of multinational firms and foreign direct investment in the region. The analysis is further extended by examining the drivers, motives and operational issues pertinent to these financial conglomerates.
Keywords: Bancassurance ventures; Banking industry; Financial institutions; Insurance markets